«Ραιδεστός – Θεσσαλονίκη Αρχαιότητες σ’ ένα ταξίδι προσφυγιάς» στην Αλεξανδρούπολη (AMTh, 2020)
: [♪ Μουσική Επικοινωνης Επικοινωνίας ΥΠΑΛΕΣΕΣΕΣΕΣΕΣΕΣΕΣΕΣΕΣΕΣΕΣΕΣΕΣΕΣΕΣΕΣΕΣΕΣΕΣΕΣΕΣΕΣΕΣΕΣΕΣΕΣΕΣΕΣΕΣΕΣΕΣΕΣΕΣΕΣΕΣΕΣΕΣΕΣΕΣΕΣΕΣΕΣΕΣΕΣΕΣΕΣΕΣΕΣΕ Υπότιτλοι AUTHORWAVE